'You will be responsible to the GOC'. Stovepiping and the problem of divergent intelligence gathering networks in Northern Ireland, 1969–1975. Issue 2 (23rd February 2018) - Craig, Tony
Abstract: From the beginning of Northern Ireland's Troubles, two different strands of British intelligence were developed in Northern Ireland that failed to effectively cooperate or coordinate their efforts with one another. Though central government was aware (and often opposed) the lack of singular control over intelligence in the province, they were unable to wrest control of security intelligence from the hands of the Army and Special Branch. This problem, meant that a Security intelligence 'stovepipe' emerged and that this stovepipe operated without reference (and at times in opposition) to policy initiatives also being pursued by the UK government at the time.